Effect of the gellan-based edible coating enriched with oregano essential oil on the preservation of the ‘Tardivo di Ciaculli’ mandarin (Citrus reticulata Blanco cv. Tardivo di Ciaculli) - Liguori, Giorgia; Greco, Giuseppe; Salsi, Giulia; Garofalo, Giuliana; Gaglio, Raimondo; Barbera, Marcella; Greco, Carlo; Orlando, Santo; Fascella, Giancarlo; Mammano, Michele Massimo (Frontiers in Sustainable Food Systems, 2024)
Mandarin, a globally recognized fruit esteemed for its nutritional content and bioactive compounds, as well as aromatic qualities, faces the critical challenge of post-harvest shelf life impacting its marketability and appeal to consumers. This study aims to assess the efficacy of edible coatings in preserving "Tardivo di Ciaculli" mandarin (Citrus reticulata Blanco cv Tardivo di Ciaculli). Two distinct edible coating formulations, denoted as EC1 (comprising gellan gum, glycerol, calcium chloride, and distilled water) and EC2 (comprising gellan gum, glycerol, calcium chloride, distilled water, and 2% oregano essential oil), were subjected to comparative analysis against control samples (CTR). In the experimental trial, mandarin fruits were immersed in the respective edible coating solutions for approximately 5 minutes and promptly stored at 6 ± 1 °C. Qualitative, nutraceutical, microbiological, and sensory analyses were conducted throughout the cold storage period (7, 14, and 24 days at 6 ± 1 °C) and during three distinct shelf-life phases (I shelf-life: 7 days at 6 ± 1 °C plus 7 days at 15 ± 1 °C; II shelf-life: 14 days at 6 ± 1 °C plus 7 days at 15 ± 1 °C; III shelf-life: 24 days at 6 ± 1 °C plus 7 days at 15 ± 1 °C). Chemical analysis of the oregano essential oil in EC2 revealed the presence of 27 compounds, with carvacrol being the predominant chemical, constituting 83.42% of the total oil. The findings indicate that the application of edible coatings effectively preserved the quality parameters of mandarin fruits, minimizing weight loss and water loss. Notably, the microbiological analysis, using a culture-dependent approach, demonstrated that EC2, incorporating oregano essential oil, exhibited the capability to diminish the viability of molds throughout the entire study duration, thereby extending the shelf life of mandarin fruits.